Microwave-assisted hydrothermal synthesis of low-temperature LiCoO2 - Jähne, Carsten; Klingeler, Rüdiger (Solid state sciences, 2012)
A microwave-assisted hydrothermal synthesis route was developed for LT-LiCoO2 and compared with the conventional hydrothermal synthesis. Our X-ray diffraction, magnetisation, and electron microscopy and electrochemical studies in both cases indicate phase-pure and practically stoichiometric materials with Li-content ≥0.99. The microwave-assisted procedure allows reducing the synthesis temperature down to 170 °C which yields plate-like nano-sized LT-LiCoO2 compared to the conventionally synthesized micro-scaled material. These differences clearly show-up in the cyclic voltammetry and the galvanostatic intermittent titration technique data which are used for further characterisation of the materials. In both cases, a tiny non-stoichiometry is suggested by the presence of low-temperature small high-spin Co4+-ions. Our results show that the microwave-assisted process allows lower synthesis temperatures for practically stoichiometric LT-LiCoO2 which is associated to size-reduction of the resulting crystallites down to the nanometre-scale and a higher fraction of the competing spinel phase.